Sociodemographic factors and level of knowledge associated with the use of emergency contraception pills - Velarde Cárdenas, María Angela (2021)
Objective: To determine the sociodemographic factors and level of knowledge associated with the use of emergency oral contraception in users of the INPPARES medical center in the city of Tacna, in 2020. Material and methods: The study was basic at a correlational level, not probabilistic with a sampling for convenience of 1200 women attended in the medical center, who were surveyed to measure their level of knowledge and use of emergency contraception (EC), identifying sociodemographic factors such as age, marital status and level of education. SPSS 25 software was used for data analysis and Chi-square was used with a significance level of 95 %. Results: It was identified that 57.5 % of the surveyed women have a low knowledge of emergency oral contraception compared to 7.6 % with a high knowledge. Regarding the use of the EC, it was identified that 85.9 % used it at least once in their life; 47.4 % used it at least once a year; 50.6 % are between 15 and 25; 59.1 % have a secondary level education degree; and the marital status of 64.9 % is single. Conclusion: There is a relationship between the level of knowledge and sociodemographic factors associated with the use of emergency contraception.